A New Method to Develop the Primate Model of Knee Osteoarthritis With Focal Cartilage Defect - Bi, Xin; Li, Tao; Li, Min; Xiang, Shutian; Li, Junhong; Ling, Bin; Wu, Zhaoxiang; Chen, Zhong (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: Osteoarthritis (OA) is a common degenerative joint disease, and animal models have proven pivotal in investigating this disease. This study aimed to develop a primate model of OA that may be more relevant to research studies on OA in humans. Method: Twelve female rhesus macaques were randomly divided into three groups. Four animals were untreated (Control group); four were subjected to the modified Hulth method, involving cutting of the anterior and posterior cruciate ligaments, and transecting the meniscus (Hulth group); and four were subjected to the modified Hulth method combined with cartilage defect (MHCD group). Each primate was subjected to motor ability tests, and underwent arthroscopic, radiographic, morphological, and pathological observation of the knee joints at various times for up to 180 days. Results: Motor ability on Day 180 was significantly lower in the MHCD group than in the Control (P＜0.01) and Hulth (P＜0.05) groups. Radiographic and morphological examination showed that the severity of knee joint deformity and articular cartilage injury were greater in the MHCD group than in the other groups. Pathological examination showed that cartilage thickness was significantly lower in the MHCD group than in the other groups at the same time points. The Mankin score on Day 180 was markedly higher in the MHCD group than in the Hulth (P＜0.05) and Control (P＜0.001) groups. Conclusion: The MHCD model of OA closely resembles the pathophysiological processes of spontaneous knee OA in humans. The time required to develop knee OA is shorter using the MHCD model than using the Hulth method.